Coupling of surface water and groundwater nitrate-N dynamics in two permeable agricultural catchments. (December 2014) - Richards, Karl; Fenton, Owen; Watson, Catherine; MELLANDER, P.-E.; MELLAND, A. R.; MURPHY, P. N. C.; WALL, D. P.; SHORTLE, G.; JORDAN, P.
SUMMARY The current study investigated the coupling of groundwater and surface water nitrogen (N) dynamics over 3 years, and considered intensive agricultural land-management influences over this period where the risk of N loss to water was considered high. Groundwater N (as nitrate) was monitored monthly in different strata and zones in four hillslopes, two in each of two agricultural catchments of c. 10 km2, and stream water N flux was monitored sub-hourly in the catchment outlets. Field nutrient sources were connected to surface water via groundwater; the groundwater along hillslopes was seen to be influenced spatially and temporally by management, geology and weather as observed in the concentration variability of nitrate in groundwater. Based on spatio-temporal averages of nitrate-N concentration, groundwater status was considered good (at least below a maximum acceptable concentration (MAC) of 11·3 mg/l). However, zones coincident with land-use change (ploughing and reseeding, typical of a management event in intensive landscapes), showed high spatio-temporal variability in nitrate-N concentration, exceeding the MAC temporarily, before recovering. This spatio-temporal variability highlighted the need for insight into these differences when interpreting groundwater quality data from a limited number of basin-scale sampling points and occasions. In both catchments the 3-year mean nitrate-N concentration in stream water was similar to the spatio-temporal mean concentration in groundwater. The magnitude and variability of loads, however, were more related to changes in annual runoff rather than changes in annual groundwater nitrate-N status. In one wet year, nitrate-N loads exceeded 48 kg/ha from an Arable catchment and 45 kg/ha from a grassland catchment (close to double the loss in a dry year).